Method for preparing polymer nanoparticles with disulfide bonds as crosslinking points and use thereof
Patent Information
- Application Number
- CN202611454931.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
然而该技术方案仍存在性能弊端,解缠结态的纳米粒子在优化加工性能的同时,会大幅牺牲聚合物的整体力学性能,导致产品综合使用性能下降
1、传统乳液聚合制备的纳米粒子,交联点往往是不可逆的共价交联,粒子形成后,其内部结构被锁死,缺乏可调控的手段。本发明将二硫键作为交联点,利用二硫键能在还原条件下实现结构断裂,赋予纳米粒子刺激响应功能,实现“粒子-链”的特定转变。
Smart Images

Figure CN122958631A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a method for preparing polymer nanoparticles with disulfide bonds as crosslinking points and their applications. Background Technology
[0002] Polymer chain entanglement is one of the core characteristics of polymer condensed matter, a unique form of molecular chain existence in concentrated polymer solutions and melt systems, and has a decisive influence on the macroscopic physical properties and processing properties of polymers in rubbery, glassy, and viscous flow states. Currently, the industry has established a mainstream theoretical system for understanding the mechanism of polymer chain entanglement, among which the topological entanglement theory is widely accepted. This theory posits that polymer chain entanglement is essentially a geometric topological entanglement structure between long-chain molecules, preventing lateral penetration displacement between chain segments and thus significantly limiting the mobility of the polymer chains.
[0003] Topological entanglement is an inherent characteristic of long-chain polymers, possessing stable physical properties. Specifically, the chain segment span of polymer entanglement points is stable at 100-300 monomer units, and the number of entanglement points is minimally affected by temperature. Molecular chain entanglement only completely disappears when the relative molecular weight of the polymer drops below the critical entanglement molecular weight (in the tens of thousands). Due to the universality and stability of polymer chain entanglement, the flow and deformation processes of polymer melts revolve around the untangling and slippage of entangled chains. This process is also a major energy-consuming stage in polymer processing and molding. Furthermore, excessive molecular chain entanglement can easily lead to molding defects such as melt fracture, severely affecting polymer processing quality and production efficiency. Therefore, achieving controllable untangling of polymer chains, reducing processing energy consumption, and minimizing molding defects are among the core research directions in the field of polymer processing.
[0004] Currently, the industry has developed various polymer deentanglement technologies, mainly including conventional methods such as low-temperature freeze-drying, shear deformation, and tensile deformation. However, existing traditional deentanglement technologies have significant technical shortcomings, generally suffering from high operating energy consumption and poor stability of the deentangled structure, making it difficult to achieve long-term and stable polymer deentanglement effects. To address these issues, existing technologies further employ microemulsion polymerization to prepare deentangled polymer nanoparticles. This method can prepare stable deentangled nanoparticles with a particle size of 15nm~30nm, effectively avoiding the instability defects of traditional deentanglement processes and significantly reducing polymer processing energy consumption. However, this technical solution still has performance drawbacks. While optimizing processing performance, the deentangled nanoparticles significantly sacrifice the overall mechanical properties of the polymer, leading to a decline in the overall performance of the product.
[0005] To address the mechanical property deficiencies of microemulsion polymerization deentanglement technology, existing research has proposed an improvement scheme: by introducing disulfide bond crosslinking points with fracture characteristics into soft nanoparticles, relying on the property that disulfide bonds can be effectively broken under various conditions, a structural transformation of polymer chain deentanglement-reentanglement is achieved, thereby balancing the polymer's processing and mechanical properties. Summary of the Invention
[0006] In view of this, the present invention provides a method for preparing polymer nanoparticles with disulfide bonds as crosslinking points and their uses. The polymer nanoparticles containing disulfide bonds are dispersed in a solvent system, and DTT is introduced as a reducing agent to break the disulfide bonds, thereby changing the structural network of the polymer.
[0007] This invention is achieved through the following technical solution: A method for preparing polymer nanoparticles with disulfide bonds as crosslinking points, comprising the following steps: The surfactant and deionized water are mixed to obtain a surfactant solution; A photoinitiator, a crosslinking agent containing disulfide bonds, and a hydrophobic polymer monomer are mixed and added to the surfactant solution. The mixture is stirred to fully emulsify, then deoxygenated, and polymerized under ultraviolet light to obtain polymer nanoparticles with disulfide bonds as crosslinking points.
[0008] As a preferred embodiment, the mass ratio of the surfactant, polymer monomer, photoinitiator, and disulfide-containing crosslinking agent is (5~6):(3~4):(0.006~0.008):(0.1~0.2).
[0009] As a preferred embodiment, the crosslinking agent containing disulfide bonds includes di(2-(4-vinylbenzoyloxy)ethyl)disulfide.
[0010] As a preferred embodiment, the surfactant comprises at least one of dodecyltrimethylammonium bromide and sodium dodecyl sulfate; and / or, the photoinitiator comprises at least one of 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; and / or, the polymer monomer comprises styrene.
[0011] The application of polymer nanoparticles with disulfide bonds as crosslinking points, as described above, in polymer chain deentanglement-reentanglement.
[0012] A method for de-entanglement and re-entanglement of polymer chains includes the following steps: The polymer nanoparticles with disulfide bonds as crosslinking points obtained by the aforementioned preparation method are mixed with dithiothreitol, so that the polymer nanoparticles with disulfide bonds as crosslinking points change from a state of unentanglement to a state of reentanglement under the reducing action of the dithiothreitol.
[0013] As a preferred embodiment, the amount of dithiothreitol added is 5% to 25% of the mass of the polymer nanoparticles with disulfide bonds as crosslinking points.
[0014] The principle of this invention is that, with disulfide bonds as crosslinking points, the polymer nanoparticles use disulfide bonds as nodes for intramolecular crosslinking, and nanoparticles with untangled molecular chains are prepared by microemulsion polymerization. The nanoparticles undergo reduction by dithiothreitol (DTT), resulting in the breaking of disulfide bonds and the disconnection of cross-linking points, thus transforming them from nanoparticles into entangled chains. Polymer chains can undergo intermolecular topological reentanglement, which increases the viscosity of the system and further elongates the entanglement plateau of the master rheological curve.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Nanoparticles prepared by traditional emulsion polymerization often have irreversible covalent crosslinking points. After particle formation, their internal structure is locked, lacking controllable means. This invention uses disulfide bonds as crosslinking points and utilizes the ability of disulfide bonds to achieve structural breakage under reducing conditions, endowing nanoparticles with stimulus-responsive functionality and realizing a specific "particle-chain" transformation.
[0016] 2. Processing performance requires polymer segments to be able to slide and rearrange rapidly, macroscopically manifested as low viscosity, typically requiring moderate molecular weight and low crosslinking density. However, mechanical properties necessitate strong interactions between polymer chains, such as high crosslinking density, to resist segment slippage. This inherent contradiction greatly limits the application of the material. In this invention, disulfide-linked soft nanoparticles combined with a DTT-triggered decrosslinking system construct a smart system that can freely switch between a "processing state" (nanoparticles, low entanglement) and a "service state" (linear chains, high entanglement), significantly improving the material's processing and forming performance and providing a novel approach to resolving the processing-mechanical contradiction.
[0017] 3. This invention utilizes the redox properties of disulfide bonds to achieve re-entanglement. Research has found that disulfide bonds are sensitive to multiple systems (such as high temperature, specific enzymes, or microenvironments, such as high GSH concentration in tumor cells). Therefore, these nanoparticles are expected to be used in a variety of environments and have potential "multi-responsive" intelligent foundations. Attached Figure Description
[0018] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 The image shows the proton nuclear magnetic resonance spectrum of the crosslinking agent containing disulfide bonds; Figure 2 The particle size distribution diagrams of polystyrene nanoparticles containing disulfide bonds in Examples 1 and 2, and the particle size distribution diagrams after the crosslinking points are broken under the action of DTT. Figure 3 This diagram illustrates the synthesis of soft nanoparticles containing polymer nanoparticles with disulfide bonds as crosslinking points in Examples 1 and 2, and the structural changes after the crosslinking points break. Figure 4 The rheological master curves of crosslinking point fracture before and after DTT in Examples 1 and 2 are shown (the entanglement plateau increases from short to long and from non-existent to present, indicating that re-entanglement transformation can be achieved). Figure 5 The graph shows the viscosity changes before and after the crosslinking point breaks under DTT in Examples 1 and 2 (low viscosity is beneficial for polymer processing, and the viscosity increases after the crosslinking point breaks, which increases the mechanical properties). Figure 6 The image shows the Raman spectrum of the disulfide-containing crosslinking agent prepared in this application. Detailed Implementation
[0019] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0020] In the following examples, the crosslinking agent containing disulfide bonds was prepared using the following method: 4-Vinylbenzoic acid (10.1 g, 68.2 mmol), dicyclohexylcarbodiimide (DCC) (13.3 g, 64.5 mmol), and 4-dimethylaminopyridine (DMAP) (7.9 g, 64.6 mmol) were added to a 250 mL round-bottom flask. Then, 100 mL of ultra-dry DCM was added to completely dissolve the precipitate. Next, di(2-hydroxyethyl) disulfide (CAS: 1892-29-1) (5 g, 32.4 mmol) was added. The mixture was stirred under nitrogen protection for 24 hours. The white precipitate was then filtered off, and the filtrate was collected. The solvent was removed by rotary evaporation. The product was purified by silica gel column chromatography using petroleum ether / ethyl acetate (v / v) as the eluent. The final product, di(2-(4-vinylbenzoyloxy)ethyl) disulfide, was obtained in a total of 7.2 g (55% yield). Its proton NMR spectrum is shown below. Figure 1 As shown, the Raman spectrum is as follows Figure 6 As shown, 508 cm -1 The peak at that point is a characteristic peak of the SS bond (reference). Ernest J. Bastian, Jr, R. Bruce Martin. Disulfide vibrational spectra in the sulfur-sulfur and carbon-sulfur stretching region. TheJournal of Physical Chemistry, 1973, 77 (9), 1129–1133 ).
[0021] 1 H NMR (400 MHz, CDCl3) δ 7.99 (d, J = 8.2 Hz, 4H), 7.44 (d, J = 8.3Hz, 4H), 6.74 (dd, J = 17.6, 10.9 Hz, 2H), 5.85 (d, J = 17.6 Hz, 2H), 5.38 (d, J = 10.9 Hz, 2H), 4.59 (t, J = 6.5 Hz, 4H), 3.09 (t, J = 6.5 Hz, 4H).
[0022] from Figure 1 As can be seen, di(2-(4-vinylbenzoyloxy)ethyl)disulfide has a symmetrical molecular structure and good purity. The specific synthesis steps and structural formula are as follows:
[0023] Example 1: This example provides a method for preparing polymer nanoparticles with disulfide bonds as crosslinking points and their applications. The preparation method includes the following steps: Mix 5.30g of dodecyltrimethylammonium bromide with 60ml of deionized water and stir at room temperature for 30 minutes until fully dissolved; 3.53g of styrene, 7.06mg of 2,2-dimethoxy-2-phenylacetophenone, and 117mg of a disulfide-containing crosslinking agent (di(2-(4-vinylbenzoyloxy)ethyl)disulfide) were mixed evenly and then added to the above-mentioned aqueous solution containing surfactant. The mixture was stirred and emulsified at room temperature for 30 minutes. The emulsion was then purged with high-purity nitrogen for 30 minutes to completely remove oxygen from the aqueous solution. The fully emulsified reaction solution was placed under a UV lamp (wavelength 365nm, power 20W) to initiate polymerization for 15 minutes. After the reaction was completed, the reaction solution was poured into excess methanol to demulsify and precipitate, resulting in a white precipitate. The white precipitate was dissolved in dichloromethane (DCM), and the surfactant was removed by methanol precipitation and recycling. Finally, the obtained solid was placed in a vacuum oven and dried at 40°C for 72 hours to obtain polymer nanoparticles (D23N60, bulk particle size D) with disulfide bonds as crosslinking points. bulk = 23nm, crosslinking degree Nc = 60), particle size distribution diagram as shown in the figure. Figure 2 As shown in a, [D latex It is the emulsion particle size, D bulk =(D latex -2)nm, D bulk It is the bulk particle size, which is the emulsion particle size D. latex Subtracting the approximately 2nm thickness of the surfactant, D swo It is the swelling particle size of the nanoparticles (dissolved in THF, 2 mg / ml), D swo (SH) Particle size of the re-entangled linear chains formed after the crosslinking point breaks, also dissolved in THF, 2 mg / ml.
[0024] In this invention, the original polymer nanoparticles with disulfide bonds as crosslinking points are in a disentangled state. After adding DTT (at 5% of the mass of the polymer nanoparticles with disulfide bonds as crosslinking points), the crosslinking points break, the nanoparticles de-crosslink and form chain segments, and the chains recover and re-entangle. The specific principle is as follows: Figure 3 As shown.
[0025] D latex The emulsion particle size was determined by irradiating the emulsion with ultraviolet light for 15 minutes. After the reaction was completed, an appropriate amount of the reaction solution was diluted 20 times with deionized water, filtered through a 0.22 μm filter membrane, and then tested using dynamic light scattering (DLS, Malvern Zetasizer Nano ZS).
[0026] D bulk =(D latex -2b) = (D latex-2) nm, where b=1 originates from a 1994 research article by Professor Wu Qi published in Macromolecules. This article showed that spherical latex particles generally possess a "core-shell structure," meaning the inner "core" is composed of polymer molecules, and the outer "shell" is composed of surfactant molecules, with the hydrophobic tails of the surfactant partially inserted into the polymer core. Researchers combined static light scattering (SLS) and dynamic light scattering (DLS) to study a polystyrene model using hexadecyltrimethylammonium bromide (CTAB) as the surfactant, concluding that the thickness of the "shell" formed outside the core is approximately 1.0 ± 0.2 nm. (Reference) Wu, C. Laser Light Scattering Determination of the Surfactant Interface Thickness of Spherical Polystyrene Microlatices. Macromolecules, 1994, 27 (24), 7099−7102 .) D swo and D swo (SH) is the swelling particle size of the melt. The test method is to dissolve the obtained soft nanoparticles (D#N#) or the product of crosslinking point breakage after DTT treatment (D#N#SH) in THF at a concentration of 2 mg / ml, filter it through a 0.22 μm filter membrane, and then test it using dynamic light scattering (DLS, Malvern Zetasizer Nano ZS).
[0027] Example 2: This example provides a method for preparing polymer nanoparticles with disulfide bonds as crosslinking points and their applications. The preparation method includes the following steps: Mix 5.30g of dodecyltrimethylammonium bromide with 60ml of deionized water and stir at room temperature for 30 minutes until fully dissolved; 3.53g of styrene, 7.06mg of 2,2-dimethoxy-2-phenylacetophenone, and 175mg of a disulfide-containing crosslinking agent (di(2-(4-vinylbenzoyloxy)ethyl) disulfide) were mixed evenly and then added to the above aqueous solution containing surfactant. The mixture was stirred and emulsified at room temperature for 30 minutes. The emulsion was then purged with high-purity nitrogen for 30 minutes to completely remove oxygen from the aqueous solution. The fully emulsified reaction solution was placed under a UV lamp (wavelength 365nm, power 20W) to initiate polymerization for 20 minutes. After the reaction, the reaction solution was poured into excess methanol to demulsify and settle, resulting in a white precipitate. The white precipitate was dissolved in DCM and washed away by methanol sedimentation to remove the surfactant. Finally, the obtained solid was placed in a vacuum oven and dried at 40°C for 72 hours to obtain polymer nanoparticles (D23N40, bulk particle size D) with disulfide bonds as crosslinking points. bulk = 23nm, crosslinking degree Nc = 40), particle size distribution diagram as shown in the figure. Figure 2 As shown in b.
[0028] In this invention, the original polymer nanoparticles with disulfide bonds as crosslinking points are in a disentangled state. After adding DTT (the amount of DTT added is 25% of the mass of the polymer nanoparticles with disulfide bonds as crosslinking points), the crosslinking points break, the nanoparticles disentangle to form chain segments, and the chains recover and re-entangle.
[0029] The degree of crosslinking, Nc, is calculated based on the feed ratio of monomer to crosslinking agent. ,in This represents the molar ratio of crosslinking agent to monomer (styrene). (Reference) Ruan Y, Principle of Disentanglement by Intrachain Cross-Linking in the Melt of Soft-Nanoparticles. Macromolecules, 2025, 58 (12), 6033–6040. ).
[0030] Example 3: This example provides a method for preparing polymer nanoparticles with disulfide bonds as crosslinking points and their applications. The preparation method includes the following steps: Mix 5.30g of dodecyltrimethylammonium bromide with 60ml of deionized water and stir at room temperature for 30 minutes until fully dissolved; 3.28g of styrene, 7.06mg of 2,2-dimethoxy-2-phenylacetophenone, and 175mg of a disulfide-containing crosslinking agent (di(2-(4-vinylbenzoyloxy)ethyl) disulfide) were mixed evenly and then added to the above aqueous solution containing surfactant. The mixture was stirred and emulsified at room temperature for 30 min. The emulsion was then purged with high-purity nitrogen for 30 min to completely remove oxygen from the aqueous solution. The fully emulsified reaction solution was placed under a UV lamp (wavelength 365nm, power 20W) to initiate polymerization for 15 minutes. After the reaction, the reaction solution was poured into excess methanol to demulsify and settle, resulting in a white precipitate. The white precipitate was dissolved in DCM and washed away by methanol precipitation to remove the surfactant. Finally, the obtained solid was placed in a vacuum oven and dried at 40°C for 72 hours to obtain polymer nanoparticles with disulfide bonds as crosslinking points. In this invention, the original polymer nanoparticles with disulfide bonds as crosslinking points are in a de-entangled state. After adding DTT (the amount of DTT added is 20% of the mass of the polymer nanoparticles with disulfide bonds as crosslinking points), the crosslinking points break, the nanoparticles de-crosslink to form chain segments, and the chain entanglement is restored.
[0031] Comparative Example 1: As a control experiment of Example 1, this comparative example differs from Example 1 only in that the amount of dithiothreitol added is 3% of the mass of the polymer nanoparticles with disulfide bonds as crosslinking points, and the other operations are the same as in Example 1.
[0032] In polymer nanoparticles with disulfide bonds as crosslinking points (also known as soft nanoparticles), the disulfide bonds break under the reducing action of dithiothreitol. Although the conditions required for this breakage are relatively mild, insufficient addition of dithiothreitol cannot lead to complete breakage of the crosslinking points. In this case, the structural changes of the soft nanoparticles are possible in several ways. For example, when the crosslinking points begin to break, the soft nanoparticles further swell in the solution, increasing in size. The elongation of their entanglement plateau is due to inter-particle interactions, resulting in small changes that are difficult to observe. If the crosslinking points cannot break completely, it may only lead to the shedding of surface chains from the soft nanoparticles. In this case, the particle size decreases, and the polymer in the solution becomes a mixture of nanoparticles and linear chains, affecting the efficiency of re-entanglement. The nanoparticles prepared in the examples and comparative examples are characterized below: 1. The particle size of the disulfide-bonded polystyrene nanoparticles in Examples 1 and 2 was determined using dynamic light scattering (DLS). The test results are as follows: Figure 2 As shown.
[0033] from Figure 2 It can be seen that the emulsion particle sizes of polystyrene nanoparticles containing disulfide bonds are 25.1 nm and 25.6 nm (Dlatex); after swelling in tetrahydrofuran (THF), the particle sizes are measured to be 52.2 nm and 46.5 nm (Dswo); after adding DTT (dithiothreitol, with addition amounts of 5 wt% and 25 wt% of the mass of polystyrene nanoparticles containing disulfide bonds) to THF and reducing it at room temperature for 24 hours, the disulfide bonds break, the linear chains extend, and the particle sizes increase to 70.4 nm and 74.8 nm (Dswo(SH)), respectively. This indicates that the presence of DTT can effectively reduce disulfide bonds, causing the crosslinking points of polystyrene nanoparticles containing disulfide bonds to break.
[0034] 2. Rheological testing: (1) Add plasticizer tricresyl phosphate (TCP) (volume ratio of polystyrene nanoparticles containing disulfide bonds to tricresyl phosphate is 20:80, 29:71, 37:63, 46:54) (D#N#) to polystyrene nanoparticles containing disulfide bonds. Use TCP solution to lower the overall test temperature of the system and avoid disulfide bond exchange reaction caused by high temperature.
[0035] (2) Add 50 mg DTT to a tetrahydrofuran system containing 200 mg disulfide-bonded polystyrene nanoparticles. Adjust the alkalinity of the solution to 8 with triethylamine. Stir at room temperature for 24 h to ensure complete breakage of the disulfide bonds. Then pour the reaction solution into excess methanol to wash away excess unreacted DTT. Dry the precipitate at 40 °C for 72 h (D#N#SH). Add the plasticizer tricresyl phosphate to the product (the volume ratio of disulfide-bonded polystyrene nanoparticles to tricresyl phosphate is 20:80, 29:71, 37:63, 46:54). The test results are as follows: Figure 4 and Figure 5 As shown.
[0036] from Figure 4 It can be seen that the original disulfide-bonded polystyrene nanoparticles have no entanglement plateau or a short entanglement plateau in the low-frequency region; after the addition of DTT, the chains formed by the breakage of the crosslinking points of the nanoparticles re-entangle, and the entanglement modulus plateau reappears or is extended. Figure 5 It can be seen that the original polystyrene nanoparticles containing disulfide bonds have low viscosity. After DTT reduces the disulfide bonds, the viscosity increases significantly. This indicates that nanoparticles using disulfide bonds as crosslinking agents can achieve changes in unentangled nanoparticles and reentangled linear chains, realizing a specific "particle-chain" change.
[0037] Comparative Example 2: The only difference between this comparative example and Example 1 is that the masses of dodecyltrimethylammonium bromide, styrene, 2,2-dimethoxy-2-phenylacetophenone, and 2-(4-vinylbenzoyloxy)ethyl)disulfide are 10.7 g, 3.53 g, 7.06 mg, and 350 mg, respectively.
[0038] As can be seen from the comparison between Example 1 and Comparative Example 2, the amount of surfactant added in microemulsion polymerization can affect the size of soft nanoparticles. When the solid content of surfactant (solid content: molar ratio of surfactant to monomer) is increased, the particle size of soft nanoparticles decreases, the relative molecular weight of polymer chains formed after the crosslinking point breaks decreases, and the efficiency of re-entanglement is affected. Increasing the content of crosslinking agent (2-(4-vinylbenzoyloxy)ethyl) disulfide in microemulsion polymerization increases the degree of crosslinking of soft nanoparticles, forming dense crosslinking points. DTT molecules need to diffuse into the interior of the polymer network to access the encapsulated disulfide bonds, but the dense network structure generates huge steric hindrance, affecting the diffusion rate and reduction efficiency of DTT, ultimately leading to incomplete breakage of crosslinking points and affecting the efficiency of re-entanglement. The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing polymer nanoparticles with disulfide bonds as crosslinking points, characterized in that, Includes the following steps: The surfactant and deionized water are mixed to obtain a surfactant solution; A photoinitiator, a crosslinking agent containing disulfide bonds, and a hydrophobic polymer monomer are mixed and added to the surfactant solution. The mixture is stirred to fully emulsify the mixture, then deoxygenated and polymerized under ultraviolet light to obtain polymer nanoparticles with disulfide bonds as crosslinking points. The polymer monomer includes styrene, and the disulfide-containing crosslinking agent includes di(2-(4-vinylbenzoyloxy)ethyl)disulfide.
2. The method for preparing polymer nanoparticles with disulfide bonds as crosslinking points according to claim 1, characterized in that, The mass ratio of the surfactant, polymer monomer, photoinitiator, and disulfide-containing crosslinking agent is (5~6):(3~4):(0.006~0.008):(0.1~0.2).
3. The method for preparing polymer nanoparticles with disulfide bonds as crosslinking points according to claim 1, characterized in that, The surfactant includes at least one of dodecyltrimethylammonium bromide and sodium dodecyl sulfate; and / or the photoinitiator includes at least one of 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
4. The use of polymer nanoparticles with disulfide bonds as crosslinking points as described in claim 1 in polymer chain deentanglement-reentanglement.
5. A method for de-entanglement and re-entanglement of polymer chains, characterized in that, Includes the following steps: The polymer nanoparticles with disulfide bonds as crosslinking points obtained by the preparation method according to claim 1 are mixed with dithiothreitol, so that the polymer nanoparticles with disulfide bonds as crosslinking points change from a state of unentanglement to a state of reentanglement under the reducing action of the dithiothreitol.
6. The method for de-entanglement and re-entanglement of polymers according to claim 5, characterized in that, The amount of dithiothreitol added is 5% to 25% of the mass of the polymer nanoparticles with disulfide bonds as crosslinking points.